Pengaruh Work Life Balance dan Kesejahteraan Psikologis terhadap Keterlibatan Kerja Pegawai Kelurahan dan Kecamatan Semarang Tengah - Dessya Putri Haryanti; Mohammad Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of the study is to analyze and explain (1) the effect of work-life balance on the work involvement of employees of Kelurahan and Kecamatan Semarang Tengah (2) the effect of psychological well-being on the work involvement of employees of Kelurahan and Kecamatan Semarang Tengah. This research is a type of explanatory research. The research sample was 100 employees of the village office and sub-district of Central Semarang, Semarang City. Data collection using the google form application is sent to all respondents. Respondents who fill out a complete questionnaire become data that can be analyzed. For the purposes of data analysis, instrument tests, model tests and hypothesis tests (t tests) are carried out. The research findings are (1) Work-life balance has a positive effect on the work involvement of employees of the Kelurahan and Central Semarang sub-districts. (2) Psychological well-being has a positive effect on the work involvement of employees of Kelurahan and Central Semarang District. Based on research findings that show that work involvement is influenced by work-life balance and psychological well-being, therefore, sub-districts and sub-districts in making policies related to human resource management need to provide space for employees to build work-life balance and the formation of psychological well-being of employees.